Kepuasan Memediasi Pengaruh Physical Evidence Terhadap Minat Berkunjung di Rumah Makan Payakumbuh Veteran Bintaro, Jakarta Selatan - Adawiyah, Robiatul; Riyadi, Agus; Pangkerego, Eduard R (Universitas Islam Kadiri, 2024)
The restaurant industry in Indonesia, especially in big cities like Jakarta, experiences intense competition. Visitors not only pay attention to the quality of the food, but also the experience they get while at the restaurant. One of the factors that influences this experience is physical evidence such as cleanliness, interior design and restaurant facilities. This research aims to examine the influence of physical evidence on interest in visiting the Veteran Payakumbuh Bintaro Restaurant, with visitor satisfaction as a mediating variable. The research method used is a quantitative approach with a survey method, where data is collected through questionnaires distributed to 100 respondents. The analysis technique used is multiple linear regression and path analysis to test the direct and indirect effects between variables. The research results show that physical evidence has a significant effect on visitor satisfaction, which in turn has a positive effect on interest in visiting. Visitor satisfaction acts as a mediator in the relationship between physical evidence and visiting interest. Therefore, it is recommended that restaurant managers continue to improve the quality of physical elements to increase satisfaction and attract more visitors. This research provides insight for restaurant managers in creating enjoyable experiences and increasing customer loyalty.